Practices of anti-malaria pharmaceuticals inventory control system and associated challenges in public health facilities of Oromiya special zone, Amhara region, Ethiopia - Haile Yirga Mengesha; Getachew Moges Gebrehiwot; Birhanu Demeke Workneh; Mesfin Haile Kahissay (BMC, 2021)
Abstract Background Anti-malaria pharmaceuticals inventory control system helps to maintain an appropriate stock level using logistics management information system records and reports. Antimalaria pharmaceuticals are highly influenced by seasonality and demand variation. Thus, to compensate the seasonality, resupply quantities should be adjusted by multiplying the historical consumption with the Look-ahead seasonality indexes (LSI) to minimize stock-outs during the peak transmission season and overstocks (possible expiries) during off-peak seasons The purpose of this study was to assess anti-malaria pharmaceuticals inventory control practice and associated challenges in public health facilities of the Oromiya special zone, Amhara region, Ethiopia. Methodology Facility-based cross-sectional study design employing both quantitative and qualitative methods, explanatory sequential mixed method, of data collection and analysis was used in all public health facilities in the Oromia special zone from September 1 to September 30, 2019. The study was conducted in 27 health centers and 2 hospitals, the dispensing units managing anti-malaria pharmaceuticals and data was collected using observation checklists The quantitative data were analyzed by Statistical package for social sciences using linear regression. Purposive sampling was used to select key informants and 12 in-depth interviews were conducted by the principal investigator. Thematic analysis was performed using Nvivo 11 plus and interpretation by narrative strategies. Results The quantitative finding in this study revealed that none of the health facilities surveyed calculated months of stock and multiplied the historical consumption with look ahead seasonal indices (LSI) to forecast the upcoming year consumptions.. Average months of stock of anti-malaria pharmaceuticals were 5.32 months with the annual wastage rate of 11.32%. The point and periodic availability of anti-malaria pharmaceuticals was 72.38 and 77.03% respectively. The number of stocks out days within the previous 6 months was 41.34 days. The study also reported bin card usage (β = − 3.5, p = 0.04) and availability of daily dispensing register (β = − 2.7, p = 0.005) had statistically significant effect on anti-malaria pharmaceuticals inventory control practice. The perceived challenges attributed to the poor anti-malaria pharmaceuticals inventory control practice were lack of integrated pharmaceutical logistics system training, management support, inadequate and near expiry supply from pharmaceuticals supply agency, job dissatisfaction, and staff turnover. Conclusion Inventory control practices for anti-malaria pharmaceuticals was poor as indicated by maximum stock level and none of the health facilities calculated months of stock and the previous consumption was not multiplied by look ahead seasonal indices to compensate the seasonal and demand variation. Efforts should be under-taken by concerned bodies to improve inventory control practice; such as training and regular follow up have to be provided to the health professionals managing anti-malaria pharmaceuticals.